Pamilya si yaya celebrating the yaya and alaga narrative through a children's storybook targeted towards children ages 6 to 11 and their parents to encourage empathy and appreciation for the Filipino yaya - Velmonte, Jeremiah M.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
The yaya is a vital part of the urabn Filipino family. As the economy pushes both parents to look for full-time occupation to provide for their families, yayas are the ones who step in to handle household matters left behind. This include tasks like cooking, cleaning, and care giving. Yayas also pursue their occupation with the primary goal of securing a better source of income for their families. To become a yaya entails a lot of challenges for a woman. Yayas who are mothers would have to face the struggle of being far from their loved ones, especially their own children. Leaving their children behind would bring about a certain degree of disconnect as yayas would have to tend to her employer's child instead. Therefore, they would have to deal with a deteriorating relationship with their very own children. It is also an uncertainty on whether yayas get into households who will treat them right or not as the domestic industry lacks structure. This lack in structure also extends to how employers enforce labor practices. This can be seen in the inflexibility of how much they pay the yayas and how many hours a yaya is required to work. Yayas are also viewed lowly as they are considered to be uneducated and untrained so there is urgency to provide them higher wages. Indeed, being a yaya brings with it many struggles for a woman. Nonetheless, the practice of hiring yayas allow for developments between her and the alaga to happen. As yayas are left to take in the roles of parents while they are away, children tend to have more time with their yayas and start to develop strong attachments with them. For some yayas who are mothers, they become a source of comfort as they allow for bonds to develop that resembles that with their own children. Some children become a yaya's silver lining in the midst of the challenge of providing for her family and the numerous amount of work she has to accomplish. yayas are very important yet they tend to be undervalued for their contribution to the family. This can be seen through a lack of support in providing better working conditions. That is why it is important to foster empathy and appreciation for them because yayas who stay with families for a long time are more than just workers, they act as secondary mothers to children as some alagas are very close to their yayas. This study aims to develop an illustrated storybook that will depict a yaya's struggle and the relationship she forms with her alaga. It aims to provide a different angle as to how people view yayas who have been with families for a long time with the hope of fostering empathy and appreciation for them as they work hard to provide for their families and at the same time care for children left at home.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 199-200.
Keywords: Women household employees -- Philippines